Association of high serum soluble interleukin 2 receptor levels with risk of adverse events in cardiac sarcoidosis. (12th September 2021) - Kobayashi, Yuta; Sato, Takuma; Nagai, Toshiyuki; Hirata, Kenji; Tsuneta, Satonori; Kato, Yoshiya; Komoriyama, Hirokazu; Kamiya, Kiwamu; Konishi, Takao; Omote, Kazunori; Ohira, Hiroshi; Kudo, Kohsuke; et al.
Abstract: Aims: Although soluble interleukin 2 receptor (sIL‐2R) is a potentially useful biomarker in the diagnosis and evaluation of disease severity in patients with sarcoidosis, its prognostic implication in patients with cardiac sarcoidosis (CS) is unclear. We sought to investigate whether sIL‐2R was associated with clinical outcomes and to clarify the relationship between sIL‐2R levels and disease activity in patients with CS. Methods and results: We examined 83 consecutive patients with CS in our hospital who had available serum sIL‐2R data between May 2003 and February 2020. The primary outcome was a composite of advanced atrioventricular block, ventricular tachycardia or ventricular fibrillation, heart failure hospitalization, and all‐cause death. Inflammatory activity in the myocardium and lymph nodes was assessed by 18 F‐fluorideoxyglucose positron emission tomography/computed tomography. During a median follow‐up period of 2.96 (IQR 2.24–4.27) years, the primary outcome occurred in 24 patients (29%). Higher serum sIL‐2R levels (>538 U/mL, the median) were significantly related to increased incidence of primary outcome ( P = 0.037). Multivariable Cox regression analysis showed that a higher sIL‐2R was independently associated with an increased subsequent risk of adverse events (HR 3.71, 95% CI 1.63–8.44, P = 0.002), even after adjustment for significant covariates. sIL‐2R levels were significantly correlated to inflammatory activity in lymph nodes ( r = 0.346, P = 0.003) but not the myocardium ( r = 0.131, P = 0.27). Conclusions: Increased sIL‐2R is associated with worse long‐term clinical outcomes accompanied by increased systemic inflammatory activity in CS patients.